2018
DOI: 10.2495/sdp-v13-n1-96-107
|View full text |Cite
|
Sign up to set email alerts
|

The use of HBIM models as a tool for dissemination and public use management of historical architecture: A review

Abstract: Disseminating detailed and accessible information about the built heritage is fundamental to help understand the value and meaning of that heritage to society. Recent research highlights the potential of the Historic Building Information Modeling (HBIM) system for managing and disseminating heritage. However, this area is still in an early stage of development. This study aims to present a state-of-the-art review on the use of HBIM for both disseminating the value of historic architecture and managing the publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
(31 reference statements)
1
15
0
1
Order By: Relevance
“…At the same time, this tool could be interactive, so as to guarantee the collaboration of different players, each one with his own expertise. The limit shown by these Italian studies, moreover few in number, is the application of a conventional BIM approach, the same developed for new constructions, whereas it could have been necessary to merge this approach with methodologies studied for historical heritage, recently known as HBIM (Murphy et al, 2009;Oreni et al, 2014;Volk et al, 2014;Dore and Murphy, 2015;Brusaporci et al, 2018;López et al, 2018;Pocobelli et al, 2018;Salvador García et al, 2018). Murphy affirms that HBIM is "a novel prototype library of parametric objects, based on historic architectural data and a system of cross platform programmes for mapping parametric objects onto point cloud and image survey data" (Murphy et al, 2009), whereas other researchers state that it is "a multidisciplinary system consisting in the construction of smart objects (parameterized on the basis of architectural rules and treatises) on the data deriving from the building survey" (Brusaporci et al, 2018).…”
Section: The Proposal Of a Hbim Methods For Steel Architectural Heritagementioning
confidence: 99%
“…At the same time, this tool could be interactive, so as to guarantee the collaboration of different players, each one with his own expertise. The limit shown by these Italian studies, moreover few in number, is the application of a conventional BIM approach, the same developed for new constructions, whereas it could have been necessary to merge this approach with methodologies studied for historical heritage, recently known as HBIM (Murphy et al, 2009;Oreni et al, 2014;Volk et al, 2014;Dore and Murphy, 2015;Brusaporci et al, 2018;López et al, 2018;Pocobelli et al, 2018;Salvador García et al, 2018). Murphy affirms that HBIM is "a novel prototype library of parametric objects, based on historic architectural data and a system of cross platform programmes for mapping parametric objects onto point cloud and image survey data" (Murphy et al, 2009), whereas other researchers state that it is "a multidisciplinary system consisting in the construction of smart objects (parameterized on the basis of architectural rules and treatises) on the data deriving from the building survey" (Brusaporci et al, 2018).…”
Section: The Proposal Of a Hbim Methods For Steel Architectural Heritagementioning
confidence: 99%
“…Estos beneficios han animado el análisis de la aplicación del entorno BIM en el marco del patrimonio cultural, derivándose de ella el concepto de HBIM (Murphy, McGovern y Pavia 2009). Son variadas las revisiones sobre el tema realizadas hasta la fecha, centradas en el modelado y la implantación en plataformas BIM (Pocobelli et al 2018), en la tecnología y los componentes BIM (Logothetis, Delinasiou y Stylianidis 2015), en los distintos enfoques metodológicos y las herramientas (López et al 2018), en las dimensiones y niveles de madurez (Merchán et al 2018), en los usos y los protocolos (Jordan et al 2018;Salvador, García-Valldecabres y Viñals 2018), así como en los gemelos digitales y la conservación preventiva (Jouan y Hallot 2020). Sin embargo, no se ha reflexionado sobre la creación del modelo HBIM partiendo de las características específicas y valores propios de la arquitectura histórica, vacío que pretende abordar este trabajo.…”
Section: Bim Y Patrimonio Culturalunclassified
“…HBIM involves multiple stakeholders that usually work in different geographic locations, which makes collaboration challenging. Therefore, different authors have suggested that a possible solution would be the creation of a Common Data Environment (CDE) to synchronise information in real time (Du et al, 2018;Li et al, 2018;Salvador García et al, 2018;Oreni et al, 2014). The CDE is discussed in the next session.…”
Section: Literature Synthesismentioning
confidence: 99%